Social Support and Self-Adjustment of Students with Disabilities at State Universities in Padang / Dukungan Sosial dan Penyesuaian Diri Mahasiswa Disabilitas Universitas Negeri di Kota Padang - Ardias, Widia Sri; Hakim, Luqmanul; Aqila, Fikratul (Psikoislamika: Jurnal Psikologi Islam, 2020)
Abstract: One of the successes of humans in adapting to their environment is the existence of social support in every challenging life process. For students, this challenge is closely related to the completion of academic assignments and the dynamics of interactions that occur in campus life. Students with disabilities face tougher challenges, in which they are not only charged with academic burdens but also have to struggle to break through the limits of their physical disabilities. The present study explains the relationship between social support and self-adjustment of students with disabilities at State Universities in Padang. The research design used was a quantitative method. In addition, by using total sampling technique, the sample of this study involved seventeen students with disabilities at State Universities in Padang. Furthermore, the discussion in this study also used an Islamic perspective, in which a study of the Quran was applied in finding out the relationship between the two research variables. The results of the study showed that there is a significant relationship between social support and self-adjustment of students with disabilities at the State University in Padang with a significance value of 0.000 (0.000 0.05) and the Pearson correlation coefficient value of 0.856. The value of R square showed the number of 0.732, which means that the contribution of social support to adjustment is 73.2%. This result is in line with the explanation of Quran, especially in Surah At-Tin verse 4 and Al Baqarah verse 286.Keywords: Social Support; Self-Adjustment; Students with DisabilitiesAbstrak: Salah satu keberhasilan manusia menyesuaikan diri dengan lingkungannya adalah adanya dukungan sosial dalam setiap proses kehidupan yang penuh tantangan. Pada mahasiswa tantangan ini erat kaitannya dengan penyelesaian tugas-tugas akademiknya dan dinamika interaksi yang terjadi dalam kehidupan kampus. Tantangan lebih berat dihadapi oleh mahasiswa disabilitas yang dituntut dengan beban akademik namun juga harus berjuang menembus batas kekurangan fisik yang dimilikinya. Penelitian ini menjelaskan hubungan antara dukungan sosial dengan penyesuaian diri mahasiswa disabilitas Universitas Negeri di Kota Padang. Metode penelitian yang digunakan adalah metode kuantitatif. Sampel yang diambil dari penelitian ini adalah 17 mahasiswa disabilitas. Teknik sampling pada penelitian ini menggunakan teknik total sampling. Pembahasan dalam penelitian ini juga menggunakan perspektif Islam sehingga dilakukan kajian alqurâ€™an dalam memandang hubungan antarÂ kedua variable penelitian. Hasil penelitian membuktikan bahwa terdapat hubungan yang signifikan antara dukungan sosial dengan penyesuaian diri mahasiswa disabilitas Universitas Negeri di Kota Padang. Hasil ini sejalan dengan penjelasan al-quran terutama dalam surat At-Tin ayat 4 dan Albaqarah ayat 286.Kata Kunci: Dukungan Sosial; Penyesuaian Diri; Mahasiswa